Alcohol management plans in Aboriginal and Torres Strait Islander (Indigenous) Australian communities in Queensland: community residents have experienced favourable impacts but also suffered unfavourable ones - Alan R. Clough; Stephen A. Margolis; Adrian Miller; Anthony Shakeshaft; Christopher M. Doran; Robyn McDermott; Robert Sanson-Fisher; Valmae Ypinazar; David Martin; Jan A. Robertson; Michelle S. Fitts; Katrina Bird; et al. (BMC, 2017)
Abstract Background In Australia, 'Alcohol Management Plans' (AMPs) provide the policy infrastructure for State and Commonwealth Governments to address problematic alcohol use among Aboriginal and Torres Strait Islanders. We report community residents' experiences of AMPs in 10 of Queensland's 15 remote Indigenous communities. Methods This cross-sectional study used a two-stage sampling strategy: N = 1211; 588 (48%) males, 623 (52%) females aged ≥18 years in 10 communities. Seven propositions about 'favourable' impacts and seven about 'unfavourable' impacts were developed from semi-structured interviews. For each proposition, one-sample tests of proportions examined participant agreement and multivariable binary logistic regressions assessed influences of gender, age (18-24, 25-44, 45-64, ≥65 years), residence (≥6 years), current drinking and Indigenous status. Confirmatory factor analyses estimated scale reliability (ρ), item loadings and covariances. Results Slim majorities agreed that: AMPs reduced violence (53%, p = 0.024); community a better place to live (54%, 0.012); and children were safer (56%, p < 0.001). More agreed that: school attendance improved (66%, p < 0.001); and awareness of alcohol's harms increased (71%, p < 0.001). Participants were equivocal about improved personal safety (53%, p = 0.097) and reduced violence against women (49%, p = 0.362). The seven 'favourable' items reliably summarized participants' experiences of reduced violence and improved community amenity (ρ = 0.90). Stronger agreement was found for six 'unfavourable' items: alcohol availability not reduced (58%, p < 0.001); drinking not reduced (56%, p < 0.001)); cannabis use increased (69%, p < 0.001); more binge drinking (73%, p < 0.001); discrimination experienced (77%, p < 0.001); increased fines, convictions and criminal records for breaching restrictions (90%, p < 0.001). Participants were equivocal (51% agreed, p = 0.365) that police could enforce restrictions effectively. 'Unfavourable' items were not reliably reflected in one group (ρ = 0.48) but in: i) alcohol availability and consumption not reduced and ii) criminalization and discrimination. In logistic regressions, longer-term (≥ 6 years) residents more likely agreed that violence against women had reduced and that personal safety had improved but also that criminalization and binge drinking had increased. Younger people disagreed that their community was a better place to live and strongly agreed about discrimination. Current drinkers' views differed little from the sample overall. Conclusions The present Government review provides an opportunity to reinforce 'favourable' outcomes while targeting: illicit alcohol, treatment and diversion services and reconciliation of criminalization and discrimination issues.